MEGAXENOLITH OF COESITE ECLOGITE FROM THE UDACHNAYA KIMBERLITE PIPE - Spetsius Z.V. (My University, 1990)
Finds of coesite-bearing parageneses in kimberlite pipes both among inclusions in diamonds and as components of deep-seated xenoliths consisting primarily of kyanite eclogite are important because of the properties of coesite itself, a characteristic barophile mineral that allows the boundary conditions of xenolith formation in the mantle to be determined. Therefore, new finds of xenoliths with coesite are obviously important. Our detection of a coesite-bearing kyanite eclogite xenolith of unique size in the Udachnaya pipe is all the more interesting because such large xenoliths are extremely rare among mantle rocks of the eclogite series, nor have any analogous specimens with kyanite or coesite yet, been described. The rock is massive, slightly banded, granoblastic and coarse grained. Its primary modal composition is: garnet 41.7 vol. percent, clinopyroxene 48.5, coesite 5.4, kyanite 3.7, rutile 0.5, sulfides 0.2.